2011
DOI: 10.1088/0957-4484/22/24/245701
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule switching with non-contact atomic force microscopy

Abstract: We report upon controlled switching of a single 3,4,9,10-perylene tetracarboxylic diimide derivative molecule on a rutile TiO 2 (110) surface using a non-contact atomic force microscope at room temperature. After submonolayer deposition, the molecules adsorb tilted on the bridging oxygen row. Individual molecules can be manipulated by the atomic force microscope tip in a well-controlled manner. The molecules are switched from one side of the row to the other using a simple approach, taking benefit of the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…By varying the number of surface hydroxyls, the authors were able to conclude that the molecules are most likely pinned by surface defects. Moreover, the authors demonstrated that the molecules could be switched from the tilted geometry at one side of the bridging oxygen row to their mirror reflections in a controlled manner using a non-contact atomic force microscope at room temperature [50]. …”
Section: Polyaromatic Derivatives With Functionalized Groupsmentioning
confidence: 99%
“…By varying the number of surface hydroxyls, the authors were able to conclude that the molecules are most likely pinned by surface defects. Moreover, the authors demonstrated that the molecules could be switched from the tilted geometry at one side of the bridging oxygen row to their mirror reflections in a controlled manner using a non-contact atomic force microscope at room temperature [50]. …”
Section: Polyaromatic Derivatives With Functionalized Groupsmentioning
confidence: 99%
“…4,5 Molecular switches are characterized by a bistable configuration, such as the charge state [6][7][8][9][10][11] or the conformation of a molecule. [12][13][14][15] The bistability can be reversibly controlled externally, for instance by supplying an interaction force, 16,17 light, [18][19][20] electrons, [21][22][23] or even by inducing a single proton transfer. 24,25 Nowadays, scanning tunneling-(STM) and atomic force microscopy (AFM) techniques [26][27][28] serve as unique tools to address and control molecular properties at the nanoscale.…”
mentioning
confidence: 99%
“…Although atomic manipulation with NC-AFM is now well established 19 , manipulation of molecules is still very much an emerging field of study. Whilst a small number of groups have reported molecular manipulation with NC-AFM (for example 20 21 ), very few have recorded the forces involved, and generally only relatively simple molecules have been investigated.…”
mentioning
confidence: 99%